An analysis of codeswitching in Welsh-language music - GERAINT THOMAS (2024)
Despite the increasing interest in codeswitching, the use of codeswitches in song lyrics remains under researched. This study is the first to focus on codeswitching in the context of Welsh-language music and focuses on the Welsh-English language pairing, investigating the extent of codeswitching, the grammatical categories of the codeswitches and their functions in the context of song lyrics. As well as improving the understanding of codeswitching in lyrics, this project presents new methods of sourcing research data in these contexts. The data sample for this project was collected through a compiled database of Welsh language music; the lyrics of six songs were analysed alongside parallel translations to contextualise the codeswitches as they occurred, as well as the poetic and discursive functions of these codeswitches. The findings suggest there is a preference among artists for certain grammatical classes, such as nouns, and certain functions, such as the alteration of rhythm, where there is a preference to codeswitch words which have fewer syllables into the lyrics. This dissertation also investigates the use of codeswitching as a method of discussing taboo, the creation of different levels of intimacy between the artist and the audience, and the demonstration of identity. Additionally, the findings provide suggestions for future research in this field, for example how conflict sites (the location of conflicting syntax between two languages) are dealt with in lyrics which feature codeswitching.